2016
DOI: 10.1002/macp.201500495
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amide Groups on the Thermal and Optical Properties of Poly(amide‐imide)s with Low Residual Stress for Microelectronic Devices

Abstract: In this study, poly(amide-imide)s are synthesized for electronic materials by adding amide groups into polyimide. As it is expected, poly(amide-imide) shows an amorphous structure with a lower glass transition temperature and residual stress than the neat polyimide due to the high steric hindrance of the amide group. Also, the modifi cation to the polyimide structure leads to higher transmittance and enhances colorless properties. Consequently, successful synthesis of poly(amide-imide) s is demonstrated which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Apart from CTE mismatch, the high residual stress after curing is also one of the important reasons to destroy the adhesion of PI and Cu. [ 22b ] On the whole, residual stress is composed of intrinsic stress and thermal stress. [ 31 ] PI after spin‐coating and curing on the surface of the substrate would generate large intrinsic stress at the interface resulted from the volume shrinkage and the limitation of the movement of the molecular chain caused by the evaporation of the solvent during the thermal imidization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from CTE mismatch, the high residual stress after curing is also one of the important reasons to destroy the adhesion of PI and Cu. [ 22b ] On the whole, residual stress is composed of intrinsic stress and thermal stress. [ 31 ] PI after spin‐coating and curing on the surface of the substrate would generate large intrinsic stress at the interface resulted from the volume shrinkage and the limitation of the movement of the molecular chain caused by the evaporation of the solvent during the thermal imidization.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] PI after spin‐coating and curing on the surface of the substrate would generate large intrinsic stress at the interface resulted from the volume shrinkage and the limitation of the movement of the molecular chain caused by the evaporation of the solvent during the thermal imidization. [ 22b,c ] Moreover, the original molecular structure and inherent physical properties of PIs are also important for intrinsic stress. On the other hand, thermal stress (σ f ) according to the following function σnormalf=140%trueTrTmEf1vnormalfαfαs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, moieties which can prompt inter-and intra-molecular interactions, such as amide, pyridine, pyrimidine, benzimidazole, have been introduced into CPIs to improve their mechanical properties and dimensional stability. [29][30][31] For instance, Hasegawa et al developed a series of CPIs through the combination of CBDA, 6FDA, TFMB, and novel ester or amide-containing monomers. Some of these CPIs with amide moieties exhibited good solubility in organic solvents, low CTE (<15 ppm K À1 ), excellent optical transparency, and high tensile strength (up to 278 MPa), modulus (>6 GPa), and elongation-at-break (>10%).…”
Section: Introductionmentioning
confidence: 99%
“…Han et al 20,21 studied the relationship between residual stress and adhesion strength of polyimide films with different chemical backbone structures. The results showed that 3,3′,4,4′‐benzophenonetetracarboxylic dianhydride (BTDA) ‐ 4,4′‐diaminodiphenyl ether (ODA) polyimide exhibited low residual stress and good adhesion to copper.…”
Section: Introductionmentioning
confidence: 99%